Dampak Penanaman Pohon Cemara Udang (Casuarina equisetifolia) di Pesisir Pantai Legend Pademawu Pamekasan terhadap Aspek Lingkungan Pesisir dan Sosial Masyarakat - Firdaus, Febry Jawahirul; Argus; Ananta, Irawan Deny (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2024)
Planting Casuarina equisetifolia trees in coastal areas has become an attention issue in recent years. Casuarina equisetifolia trees has potential impacts to reduce coastal erosion besides aesthetic benefits. Sandy beach areas have major problems, including continuous wind erosion. The aim of this research is to determine the impact of planting Casuarina equisetifolia trees on the Legend Pademawu coastal environment and its socio-economic impact on the community. This research uses field observation and structured interviews (qualitative descriptive) methods. The results of this research are that the Casuarina equisetifolia tree has a positive impact on the environment, making new form ecosystems, fertilize the soil, improve air quality, act as a water filter and improve water quality. The socio-economic impact is an increase in the tourism sector because the beach has a good aesthetic appearance and becomes a wind abrasion shield for food and baverages sellers around the beach. So the conclution of this research are the Casuarina equisetifolia trees had a positive impact on the environment and socio-economics of the community.